Apps “SIPITUNG”: Flipped-classroom training in basic cardiopulmonary life support - Wulandari, Angernani Trias; Mintaroem, Karyono; Suharsono, Tony (Universitas Muhammadiyah Purwokerto, 2020)
Background: The high number of Out of Hospital Cardiac Arrest (OHCA) worldwide, and Indonesia is not followed by high life expectancy and bystander. The role of bystander influences the high life expectancy on OHCA. The flipped learning method can increase knowledge and skills and the success of flipped learning.Objective: This study aimed to develop and test Aplikasi Hadapi Henti Jantung (Sipitung) app on the flipped classroom method in learning Basic Life Support more effectively to increase knowledge, skills, and self-efficacy.Method: The design of this research was Research and Development (R&D). This design consisted of 3 stages; stage I (literature study), stage II (application development), and stage III (application trial).Results: Based on the results of the literature review conducted following the American Heart Association guidelines on cardiac arrest, basic life support on adults required learning media that combines text, video, and audio. 4 features were included in developing and creating applications. In the experimental process, the researchers compared learning methods using flipped classroom with simulations in increasing knowledge, skills, and self-efficacy.Conclusion: